An image enhancement method based on gabor filtering in wavelet domain and adaptive histogram equalization - Jeevan K M; Anne Gowda A B; Padmaja Vijay Kumar (Institute of Advanced Engineering and Science, 2021)
The images are not always good enough to convey the proper information. The image may be very bright or very dark sometime or it may be low contrast or high contrast. Because of these reasons image enhancement plays important role in digital image processing. In this paper we proposed an image enhancement technique in which Gabor and median filtering is performed in wavelet domain and Adaptive Histogram Equalization is performed in spatial domain. Brightness and contrast are the two parameters used for analyzing the performance of the proposed method